How soon after myocardial infarction should plasma lipid values be assessed?. Issue 6459 (15th December 1984) - Ryder, R E; Hayes, T M; Mulligan, I P; Kingswood, J C; Williams, S; Owens, D R
Abstract : Because acute myocardial infarction may affect plasma lipid concentrations it is commonly recommended that assessment of these concentrations should be delayed until about three months after the acute event. A study was therefore conducted of fasting plasma lipid concentrations in 58 patients with acute myocardial infarction. Measurements were made during their stay in hospital (days 1, 2, and 9) and three months later. Triglyceride concentrations remained unchanged throughout. Values of total cholesterol, low density lipoprotein, and high density lipoprotein all fell significantly between the first two days and day 9. Total cholesterol and low density lipoprotein also showed significant falls between days 1 and 2. Nevertheless, fasting plasma lipid concentrations showed no significant difference at any time during the first 48 hours from values measured three months later. After the infarction 26 patients changed to eating less fat or less energy, or both. More patients had hypercholesterolaemia in the first 48 hours than at three months. These results suggest that lipid state may be assessed as accurately, and possibly more accurately, during the first 48 hours after acute myocardial infarction than at three months.